Novel wolf-toothed forceps for single-piece intraocular lens scleral fixation in astigmatic aphakic eyes - Jianhui Zhang; Shancheng Si; Liu Zhang (Scientific Reports)
Abstract This study introduces an innovative surgical instrument, the “wolf-toothed forceps,” and evaluates its clinical application in conjunction with the Z.S. fixation technique for managing aphakic eyes with significant corneal astigmatism lacking lens capsule support. This was a pilot, case series, and interventional study. The novel “wolf-toothed forceps,” integrated with the Z.S. fixation technique, was applied to astigmatic aphakic eyes requiring secondary toric intraocular lens (IOL) implantation. Ophthalmological examinations were performed in all patients, including slit-lamp photography and swept-source optical coherence tomography, for quantitative assessment of toric IOL position. The visual acuity measurements were converted to the logarithm of the minimum angle of resolution (log MAR) units for analysis. Eleven eyes of 11 patients with significant corneal astigmatism (1.58 ± 0.52 diopters [D]) lacking lens capsule support were enrolled. At 1-month visit postoperatively, the outcomes demonstrated significant visual improvement, with the uncorrected distance visual acuity (UDVA) of 0.47 ± 0.26 log MAR, and the best-corrected visual acuity (BCVA) of 0.29 ± 1.23 log MAR. Refractive outcomes showed excellent astigmatic correction, reducing mean whole-eye residual astigmatism to 0.30 ± 0.28 D (P < 0.001). The swept-source optical coherence tomography showed favorable stability (tilt: 5.12 ± 1.27°; decentration: 0.25 ± 0.14 mm). During the 6-month follow-up period, no severe complications related to the novel “wolf-toothed forceps” or Z.S. fixation technique were found. Our pilot study demonstrates that the wolf-toothed forceps combined with Z.S. fixation technique provides effective and safe single-piece toric IOL scleral fixation in complex aphakic eyes with significant corneal astigmatism lacking lens capsule support, achieving predictable refractive correction and stable visual rehabilitation without serious postoperative complications. The technique shows particular promise for cases where traditional IOL scleral fixation is not feasible.